The Unique Predisposition to Criminal Violations in Frontotemporal Dementia - Mendez, Mario F. (2010)
Brain disorders can lead to criminal violations. Patients with frontotemporal dementia (FTD) are particularly prone to sociopathic behavior while retaining knowledge of their acts and of moral and conventional rules. This report describes four FTD patients who committed criminal violations in the presence of clear consciousness and sufficiently intact cognition. They understood the nature of their acts and the potential consequences, but did not feel sufficiently concerned to be deterred. FTD involves a unique pathologic combination affecting the ventromedial prefrontal cortex, with altered moral feelings, right anterior temporal loss of emotional empathy, and orbitofrontal changes with disinhibited, compulsive behavior. These case histories and the literature indicate that those with right temporal FTD retain the capacity to tell right from wrong but have the slow and insidious loss of the capacity for moral rationality. Patients with early FTD present a challenge to the criminal justice system to consider alterations in moral cognition before ascribing criminal responsibility.